Jaundice and its associated factors among neonates admitted to selected referral hospitals in southwest oromia, Ethiopia: Multi-center cross-sectional study - Gutu Belay; Asfaw Gerbi; Teka Gebremariam; Tsion Tilahun; Emebet Chimdi; Tesema Etefa (Heliyon, 2023)
Background: Jaundice is a common clinical problem during the first month of birth throughout the world. Mainly, it is the leading cause of neonatal morbidity and mortality in developing countries. Objectives: The aimed of this studied was to assess predictors of jaundice among neonates admitted to selected referral hospitals in southwest Oromia, Ethiopia, 2021. Methods: An Institutional based cross-sectional study was implemented among 205 admitted neonates at selected referral hospitals in southwest Oromia, Ethiopia from October 05 to November 5, 2021. Jimma medical center (JMC), Wollega University referral hospital (WURH), and Ambo University Referral hospital (AURH) were selected by simple random sampling technique. A pretested structured interviewer-administered questionnaire and medical record review was used to collect data. Both binary and multivariable logistic regression analyses were performed to identify factors associated with neonatal jaundice. Logistic regression analyses were performed to identify factors associated with neonatal jaundice. Statistical Significance was declared at P-value less than 0.05 in the final model, and if the confidence interval does not include the null hypothesis value. Results: The prevalence of neonatal jaundice was 20.5% (95%CI: 1.74–1.85). The mean age of neonates was 8.6 ± 7.8 days. Traditional medicine use during current pregnancy (AOR: 5.62, 95%CI: 1.07, 9.52), Rh incompatibility (AOR: 0.045, 95%CI: 0.01, 0.21), gestational age (AOR: 4.61, 95%CI: 1.05, 10.3), premature rupture of membrane (AOR: 3.76, 95%CI: 1.58, 8.93) and hypertension (mother) (AOR: 3.99, 95%CI: 1.13, 14.02) were factors significantly associated with neonatal jaundice. Conclusion: Neonatal jaundice was relatively higher in the current study. Traditional medicine use, Rh incompatibility, premature ruptures of membrane, hypertension, and preterm gestational age were factors associated with neonatal jaundice.